2016
DOI: 10.1007/s12306-016-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of neglected congenital idiopathic talipes equinovarus after walking age in Eritrea: an Italo-Eritrean cooperation

Abstract: An Italian team of orthopaedic surgeons joined Eritrean colleagues to perform a clinical study in ambulating children affected by neglected idiopathic congenital talipes equinovarus (clubfoot). This study reports the surgical strategy as well as clinical outcomes, early complications and relapse at a mid-term follow-up. Four expeditions of 7 days were organized between 2012 and 2015 from Italy to the Halibet Hospital of Asmara in Eritrea. In each expedition were included two experienced surgeons, two assistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The most common length of time was 2 weeks (11 articles, 39%) [ 21 , 26–28 , 36 , 37 , 41 , 45 , 46 , 48 ]. 9 articles did not specify the length of the trip (14%) [ 12 , 18 , 29 , 34 , 39 , 41 , 44 , 47 , 49 ]. 20 articles (69%) describe short-term trips that are recurring (return to the same location more than once) either annually, biannually, or at an unspecified periodicity [ 12 , 21 , 26–32 , 34–37 , 39 , 41 , 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common length of time was 2 weeks (11 articles, 39%) [ 21 , 26–28 , 36 , 37 , 41 , 45 , 46 , 48 ]. 9 articles did not specify the length of the trip (14%) [ 12 , 18 , 29 , 34 , 39 , 41 , 44 , 47 , 49 ]. 20 articles (69%) describe short-term trips that are recurring (return to the same location more than once) either annually, biannually, or at an unspecified periodicity [ 12 , 21 , 26–32 , 34–37 , 39 , 41 , 44 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in LMICs have shown comparable results for the outcome after PMR surgery [12,27,28]. Faldini et al have followed two cohorts in Eritrea (2-to 5-year-old) and Tanzania (6-to 9-year-old) who underwent a soft tissue intervention combined with a cuboid subtraction osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Faldini et al have followed two cohorts in Eritrea (2- to 5-year-old) and Tanzania (6- to 9-year-old) who underwent a soft tissue intervention combined with a cuboid subtraction osteotomy. Patients had good to excellent outcome based on the Laaveg-Ponseti score in respectively 91% in Eritrea after an average follow-up time of two years [ 28 ] and in 79% of the cases in Tanzania after an average follow-up time of five years [ 12 ]. Hoque et al operated on two cohorts between the ages of six months and 16 years with PMR without additional bony interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients frequently present after optimal age of treatment described by Ponseti that is two years. At this time most orthopedic surgeons feel reluctant to treat these feet conservatively and resort to surgery, which is expensive and has complications [17][18][19]1,16 .…”
Section: Introductionmentioning
confidence: 99%